2008
DOI: 10.1007/s12206-007-1115-5
|View full text |Cite
|
Sign up to set email alerts
|

Transient pressure characteristics in a pressure regulating system by using 1-D analytic valve modeling

Abstract: Typically, a Pressure Control Valve (PCV) system is constructed with 3 to 4 PCV lines in order to prepare for both a future demand increase and a continuous supply of power after an emergency shutdown of the operating line. However, some operation failure cases that do not follow the original design concepts of a PCV system have been reported in the field. In this study, an accurate 1-D PCV system numerical model was built and a 1-D compressible flow theory was introduced for analytic valve modeling to find so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Cho et al (2007) derived a force balance equation and evaluated the pressure distribution and forces acting on the top and bottom planes of the valve plug. Some studies on transient numerical models of control valves were reported by Kerh et al (1997) and Shin et al (2008), which also have significance for engineering applications. Most researchers focus on the distribution of characteristics in the valve and the flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al (2007) derived a force balance equation and evaluated the pressure distribution and forces acting on the top and bottom planes of the valve plug. Some studies on transient numerical models of control valves were reported by Kerh et al (1997) and Shin et al (2008), which also have significance for engineering applications. Most researchers focus on the distribution of characteristics in the valve and the flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…As a component for reducing and stabilizing pressure in the fluid pipeline system, the PRR is widely researched [11][12][13][14][15][16][17][18][19][20][21][22][23] for its dynamic characteristics. However, many models for gas PRR adopt some assumptions such as isothermic [12,13], isentropic [14][15][16] and linearization [15] which do not strictly agree with reality.…”
Section: Introductionmentioning
confidence: 99%
“…Their pressure differential equations are usually obtained by taking the derivative of ideal gas state equation or isentropic equation and employing isothermal process assumption [12] or isentropic process assumption [15,16] rather than by deduction from the energy equation of compressible transient flow in one-dimensional (1D) conservative form. The final forms of these models depend too much on ideal gas state equation or isentropic equation; many models either do not give comprehensive consideration to roles of various chambers [12,13,15,16,21] (usually emphasize on simulating throttling and pressure stabilizing of valve spool but give little or inadequate consideration to roles of other chambers than high-and low-pressure chambers) or adopt pressure difference-based relationship between pressure and flow rate for valve spool and orifice throttling [15][16][17][18][19][20]. Moreover, there are some researches [21][22][23] on liquid PRR in the hydraulic system which use the method of bond graph and regard the fluids as incompressible flow.…”
Section: Introductionmentioning
confidence: 99%